Heterogeneity and coexistence of oncogenic mechanisms involved in HCV-associated B-cell lymphomas. (June 2019) - Carloni, Guido; Fioretti, Daniela; Rinaldi, Monica; Ponzetto, Antonio
Abstract: The association of HCV-infection with B-lymphomas is supported by the regression of most indolent/low-grade lymphomas following anti-viral therapy. Studies on direct and indirect oncogenic mechanisms have elucidated the pathogenesis of HCV-associated B-lymphoma subtypes. These include B-lymphocyte proliferation and sustained clonal expansion by HCV-envelope protein stimulation of B-cell receptors, and prolonged HCV-infected B-cell growth by overexpression of an anti-apoptotic BCL-2 oncogene caused by the increased frequency of t(14;18) chromosomal translocations in follicular lymphomas. HCV has been implicated in lymphomagenesis by a "hit-and-run" mechanism, inducing enhanced mutation rate in immunoglobulins and anti-oncogenes favoring immune escape, due to permanent genetic damage by double-strand DNA-breaks. More direct oncogenic mechanisms have been identified in cytokines and chemokines in relation to NS3 and Core expression, particularly in diffuse large B-cell lymphoma. By reviewing genetic alterations and disrupted signaling pathways, we intend to highlight how mutually non-contrasting mechanisms cooperate with environmental factors toward progression of HCV-lymphoma.